(untitled) (Limes: Revista de Estudios Clásicos, 2023)
The main hypothesis that guides this article is that Germano’s text evidences techniques related to the narrative structure and the narrative chronology that are articulated with the aim of inviting the interlocutor to carry out the ‘experience’ of joy and confidence, and thus apprehend a set of questions of a doctrinal nature. In order to confirm it, we will carry out an analysis of the sequence of discourses that constitute its structure, of the interventions that the author himself carries out and of some techniques that appear to be used repeatedly: pause, anticipation, retrospection, repetition. With these elements, the narrator builds a story in which the account of the Dormition is only one of the central elements, which is framed by a significant dogmatic context in Byzantium. Based on the textual description, we interprete that the mentioned elements are assembled to transmit in a vivid way the message to which the author aspires.